2010
DOI: 10.1016/j.bbi.2009.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Association between depressive symptoms and fibrosis markers: The Cardiovascular Health Study

Abstract: Objective-Fibrosis plays an important role in heart failure (HF) and other diseases that occur more frequently with increasing age. Depression is associated with an increased risk of heart failure and other age-related diseases. This study examined the association between depressive symptoms and fibrosis markers in adults aged 65 years and above.Methods-Fibrosis markers and depressive symptoms were assessed in 870 participants (age=80.9 ±5.9, 49% women) using a case-control design based on heart failure status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 53 publications
2
22
0
2
Order By: Relevance
“…depression was proven to be predictive for cardiovascular mortality, which was at least partly explained by the contribution of inflammation (i.e. CRP and IL-6 levels) (Kop et al, 2010;Vaccarino et al, 2007).…”
Section: Chronic Stress and Cardiovascular Diseasementioning
confidence: 96%
See 1 more Smart Citation
“…depression was proven to be predictive for cardiovascular mortality, which was at least partly explained by the contribution of inflammation (i.e. CRP and IL-6 levels) (Kop et al, 2010;Vaccarino et al, 2007).…”
Section: Chronic Stress and Cardiovascular Diseasementioning
confidence: 96%
“…, CRP, fibrinogen, IL-10 VonKänel et al (2008),Toker et al (2005),Mommersteeg et al (2006),Kop et al (2010),Vaccarino et al (2007) Affective disorders Depression CRP, IL-6 (after additional stress exposure)Rice et al (2009), Fagundes et al (2013) Anxiety disorders CRP, IL-6, TNFa, Duivis et al (2013) Post Traumatic Stress Disorder CRP, TNFa, IL-4 Plantinga et al (2013), Spitzer et al (2010), Von Känel et al (2007), Turner et al (2013) Low socioeconomic status CRP, IL-6 (after additional stress exposure), sICAM, ET-1 Nazmi and Victora (2007), Brydon et al (2004), Hong et al (2006) Caregiver stress IL-6, CRP, D-dimer Nazmi and Victora (2007), Kiecolt-Glaser et al (2003), Von Känel et al (2006), Miller et al (2008) Loneliness/social isolation IL-6, CRP, sICAM-1 Ford et al (2006), Loucks et al (2006), Heffner et al (2011) Early life stress/childhood maltreatment CRP, fibrinogen Danese et al (2007), Rooks et al IL-6, IL-1RA, sE-selectin Schultze-Florey et al (2012), Cohen et al (2015) Anger outburst CPR, IL-6 Suarez (2004), Coccaro et al (2014) Acute laboratory stressors IL-1b, TNFa, IL-2, IL-4, IL-10, CRP Slavish et al (2015)…”
mentioning
confidence: 99%
“…51 Depression has also been linked to increased levels of cytokines (specifically CRP, IL-1, and IL-6), both in patients with and without a history of cardiac disease. 20,[52][53][54] Two studies provide evidence that inflammation associated with depression predicts the development of cardiac disease and CV mortality. In a population cohort study of 908 patients without known CVD, Kop et al 24 found that depression predicted cardiovascular mortality; controlling for inflammatory markers reduced the association by 12.7%, suggesting that inflammation modestly contributed to the effects of depression on CV mortality.…”
Section: Inflammationmentioning
confidence: 99%
“…Furthermore, Patients with left ventricular ejection fraction C55% à Calculated using Cockcroft-Gault formula neuro-hormonal mediators apart from being implicated in triggering the transcriptional mechanisms responsible for the deregulation of collagen metabolism at the same time are associated with behavioral abnormalities [33]. In a recent study, Kop et al [33] reported that depression is associated with higher CITP levels although this association was not observed in a subgroup analysis regarding CHF patients. However, in the same study, the interaction effect between depression and group status (CHF vs. controls) was not significant and the authors suggested that further investigation is required in the specific CHF subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…These endocrine and autocrine pathways in turn result in altered cardiac extracellular metabolism [30], myocyte contractile dysfunction [30], and also in peripheral vascular [30,31] and muscular dysfunction [30,32]. Furthermore, Patients with left ventricular ejection fraction C55% à Calculated using Cockcroft-Gault formula neuro-hormonal mediators apart from being implicated in triggering the transcriptional mechanisms responsible for the deregulation of collagen metabolism at the same time are associated with behavioral abnormalities [33]. In a recent study, Kop et al [33] reported that depression is associated with higher CITP levels although this association was not observed in a subgroup analysis regarding CHF patients.…”
Section: Discussionmentioning
confidence: 99%